Exercise before breakfast increases 24-h fat oxidation in female subjects - Iwayama, Kaito; Kawabuchi, Ryosuke; Nabekura, Yoshiharu; Kurihara, Reiko; Park, Insung; Kobayashi, Masashi; Ogata, Hitomi; Kayaba, Momoko; Omi, Naomi; Satoh, Makoto; Tokuyama, Kumpei (PLOS ONE, 2017)
Background Exercise performed in a postprandial state does not increase 24-h fat oxidation of male and female subjects. Conversely, it has been shown in male subjects that exercise performed in a postabsorptive state increases 24-h fat oxidation compared with that in sedentary control and that with exercise trials performed after breakfast, lunch, or dinner. There is a paucity of study evaluating the effect of exercise performed in a postabsorptive state in female subjects. Method Nine young female subjects participated in indirect calorimetry measurement over 24-h using a room-size metabolic chamber in which subjects remained sedentary or performed 60 min exercise before breakfast at 50% of V˙O2max. Exercise was accompanied by an increase in energy intake to ensure that subjects were in a similar state of energy balance over 24 h for the two trials. Findings Compared with the sedentary condition, exercise performed before breakfast increased 24-h fat oxidation (519 ± 37 vs. 400 ± 41 kcal/day). Time courses of relative energy balance differed between trials with transient negative energy balance observed before breakfast. The lowest values of relative energy balance observed during the 24-h calorimetry, i.e., transient energy deficit, were greater in exercise trials than in sedentary trials. The transient deficit in carbohydrate balance was also observed before breakfast, and magnitude of the deficit was greater in exercise trial compared to that of sedentary trial. Interpretation Under energy-balanced conditions, exercise performed in a post-absorptive state increases 24-h fat oxidation in female subjects. The effect of exercise performed before breakfast can be attributed to nutritional state: a transient deficit in energy and carbohydrate at the end of exercise.